2021
DOI: 10.3390/ijms22063115
|View full text |Cite
|
Sign up to set email alerts
|

De novo Neurosteroidogenesis in Human Microglia: Involvement of the 18 kDa Translocator Protein

Abstract: Neuroactive steroids are potent modulators of microglial functions and are capable of counteracting their excessive reactivity. This action has mainly been ascribed to neuroactive steroids released from other sources, as microglia have been defined unable to produce neurosteroids de novo. Unexpectedly, immortalized murine microglia recently exhibited this de novo biosynthesis; herein, de novo neurosteroidogenesis was characterized in immortalized human microglia. The results demonstrated that C20 and HMC3 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 87 publications
0
20
0
3
Order By: Relevance
“…Finally, to assess whether the protective activity of TSPO ligands was, at least in part, mediated by the production of anti-inflammatory steroids, 661 W cells were cotreated with the ligands (3 μM) and the inhibitor of pregnenolone synthesis (10 μM), SU10603 (inhibitor of 17α-hydroxylase/C17–20 lyase (P450c17 or CYP17A1)), which prevents the conversion of pregnenolone into deidroepiandrosterone (DHEA). , From the bar graph shown in Figure , it is possible to observe a significant reduction in the protective activity of all TSPO ligands, evidencing, in particular for PIGA823 and PIGA1138 (highly steroidogenic), cell viability values comparable to those of the stressed/untreated group (DMSO), indicating an almost total suppression of their efficacy. The residual activity maintained by PIGA720 could be ascribed to the activation of other pathways, such as an increase of cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to assess whether the protective activity of TSPO ligands was, at least in part, mediated by the production of anti-inflammatory steroids, 661 W cells were cotreated with the ligands (3 μM) and the inhibitor of pregnenolone synthesis (10 μM), SU10603 (inhibitor of 17α-hydroxylase/C17–20 lyase (P450c17 or CYP17A1)), which prevents the conversion of pregnenolone into deidroepiandrosterone (DHEA). , From the bar graph shown in Figure , it is possible to observe a significant reduction in the protective activity of all TSPO ligands, evidencing, in particular for PIGA823 and PIGA1138 (highly steroidogenic), cell viability values comparable to those of the stressed/untreated group (DMSO), indicating an almost total suppression of their efficacy. The residual activity maintained by PIGA720 could be ascribed to the activation of other pathways, such as an increase of cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…28 All these effects were shown to be mediated by the production of neurosteroids. 28,32,35,36 Based on these previously described pro-survival activities of PIGAs, the aim of the present study was to assess TSPO expression in 661 W photoreceptor cell line and to evaluate the potential of targeting TSPO for the therapeutic treatment of retinal neurodegeneration. For this purpose, the abovementioned cell line was exposed to a toxic inflammatory insult (i.e., LPS 10 μg/mL), as an in vitro model of retinal neurodegeneration, and the protective effect of a number of selected PIGAs was evaluated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this present study, KEGG pathway analysis of the transcriptome revealed that GABAergic synapses were altered in primary microglial cells from the offspring of the test dams. De novo Neurosteroidogenesis was detected in Human Microglia ( Germelli et al, 2021 ). Therefore, we confirmed that CYP11A1 overexpression in dams affected GABAA receptor subunit expression in their offspring.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that TSPO is an important participant in neurosteroid synthesis, which can promote cholesterol transmembrane transport and into the phospholipid membrane, increase the formation of progesterone and downstream neurosteroid synthesis. [4][5][6] In addition, TSPO has been reported with many other physiological functions, such as cell growth and proliferation, steroid production, bile acid synthesis, calcium flow, chemotaxis and cellular immunity, heme biosynthesis, mitochondrial respiratory apoptosis, and melanin synthesis. [7][8][9][10][11] In recent years, more and more TSPO ligands have been used in the research of neurological disease treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In the central nervous system, TSPO is mainly found in microglia, activated astrocytes, and neurons in the mammalian olfactory bulb. It has been reported that TSPO is an important participant in neurosteroid synthesis, which can promote cholesterol transmembrane transport and into the phospholipid membrane, increase the formation of progesterone and downstream neurosteroid synthesis 4–6 . In addition, TSPO has been reported with many other physiological functions, such as cell growth and proliferation, steroid production, bile acid synthesis, calcium flow, chemotaxis and cellular immunity, heme biosynthesis, mitochondrial respiratory apoptosis, and melanin synthesis 7–11 …”
Section: Introductionmentioning
confidence: 99%